Application of ultrasound-based computational fluid dynamics to modeling blood flow in the carotid bifurcation - Augst,AD; Ariff,B; Barratt,DC; Thom,SAM; Hughes,AD; Xu,XY (2005)
Atherosclerotic plaque formation has been linked to haemodynamic risk factors, such as low and oscillating wall shear stresses (WSS). Experimental and numerical methods have been developed to investigate the mechanisms involved. Computational fluid dynamics (CFD) methods have the advantages of low cost and easily manageable numerical results. In order to obtain physiologically realistic results, CFD can be linked with medical imaging methods, which allow the extraction of in vivo vascular geometry and flow data to be used as input for haemodynamic simulations. Most of the image-based CFD approaches have been based on MRI, which has the disadvantages of relatively high cost and limited availability. Hence, a novel technique based on 3D ultrasound was developed with the advantages of low cost, fast acquisition and high spatial resolution. A methodology was developed to extract geometric information from the ultrasound images, reconstruct the surfaces and generate computational grids for flow simulations of the human carotid artery bifurcation. Additionally, a scheme was devised to utilize Doppler flow information for CFD boundary conditions. Accuracy and reproducibility of the combined imaging and modeling approach were evaluated in vitro and in vivo and the developed protocol was applied to normal subjects. The main conclusion of this work is the feasibility of 3D and Doppler ultrasound based CFD simulations for clinical applications. However, there are several limitations when applying this methodology in carotid bifurcations, i.e. the location of the carotid bulb relative to the jaw bone, which obscures the ultrasound path when the bifurcation is high in the neck. Future work should focus on minimizing the limitations and improve automation and reliability of image processing and reconstruction.